2014
DOI: 10.5433/1679-0359.2014v35n4p1955
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of copper deficiency in ruminants in the semiarid region of Paraíba, Brazil

Abstract: Five outbreaks of copper deficiency in goats and one in cattle are reported in the semiarid region of the state of Paraíba, Northeastern Brazil. In four outbreaks of delayed enzootic ataxia, the goat kids showed weakness that progressed to paralysis of the four limbs and recumbency. Head tremors were also present. In another outbreak of congenital enzootic ataxia, the kids were born with paralysis due to congenital copper deficiency. The serum copper concentrations were below the reference values. Histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Thus, the deficiency of copper in animal diet causes damages to nerves due to its role in the synthesis of phospholipids. Ataxia also occurs due to deficient myelination in the spinal cord followed by lesion appearance in parts of the cerebral white matter and brain stem (Silva et al, 2014).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Thus, the deficiency of copper in animal diet causes damages to nerves due to its role in the synthesis of phospholipids. Ataxia also occurs due to deficient myelination in the spinal cord followed by lesion appearance in parts of the cerebral white matter and brain stem (Silva et al, 2014).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…In addition to myelin degeneration observed in both swine and ruminants, chromatolysis and occasional neuronal necrosis are clinically observed in small ruminants (Santos et al 2006, Guedes et al 2007, Silva et al 2014 and are not observed in pigs, which show lesions restricted to white matter more closely surrounding the ventral and lateral funiculus of the spinal cord. The ultrastructural analysis showed that the primary lesion involve axonal degeneration, and the myelin vacuolization observed in the spinal cord represent foci of periaxonal demyelination, which is similar to findings by O'Hara & Shortridge (1966) and Guedes et al (2014).…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, neurological disorders caused by copper deficiency have been reported in bovines (Riet-Correa et al 1993), sheep (Guedes et al 2007), goats (Guedes et al 2007, Silva et al 2014) and pigs (Guedes et al 2014). This study describes the epidemiological, clinical, pathological and ultrastructural findings of neurological disease caused by copper deficiency in pigs in the Northeast region of Brazil.…”
Section: Introductionmentioning
confidence: 87%
“…Copper deficiency has been recognized as a cause of neurologic diseases in offspring due to deficiency of this metal in their dams (SILVA et al, 2014). General clinical signs are tremors, incoordination, paralysis and death.…”
mentioning
confidence: 99%
“…Overall, affected animals are in poor general condition characterized by progressive weight loss which may develop into anemia, caused by the diarrhea (SILVA et al, 2014;SOUSA et al, 2017).…”
mentioning
confidence: 99%